A Qualitative Study on Ethics Education at Pharmacy Colleges in Japan Based on a Survey of Ethics Educators - Etsuko Arita; Yuko Masamura; Rieko Takehira (Pharmacy)
Background: In pharmacy education in Japan, efforts continue to develop a model for ethics education that fosters high ethical standards and the problem-solving skills essential for medical professionals. This study qualitatively analyzed the attitudes of ethics educators—those who teach ethics classes—to establish a model of ethics education for pharmacy colleges in Japan. Methods: This study analyzed open-ended responses from 32 universities to the question, “What do you think about ethics education provided by faculties of pharmaceutical sciences?” Result: The qualitative analysis revealed that ethics educators at pharmacy colleges in Japan believe in the potential of ethics education to nurture problem-solving skills and logical thinking. However, the educator’s question whether or not the students would be able to apply ethics content in clinical settings as medical professionals. Another issue is that faculties of pharmaceutical sciences lack the staff and expertise to teach ethics. In other words, the educators lack the wherewithal to break the logjam in ethics education through their efforts; hence, they are desperate for an ethics education model. Conclusions: Based on our findings, further research is needed to design strategies that can enhance the quality of pharmacy education in Japan.